Out of Hospital Antithrombotic Prophylaxis after Total Hip Replacement: Low-molecular-weight Heparin, Warfarin, Aspirin or Nothing? - Sarasin, François P.; Bounameaux, Henri (Thrombosis and Haemostasis, 2002)
Several studies have suggested that after hip replacement the risk of deep vein thrombosis and subsequent pulmonary embolism (PE) may persist for some weeks. Antithrombotic prophylaxis, however, is generally stopped at hospital discharge. Using a Markov-based decision analysis, we measured the clinical and economical consequences of extending prophylaxis after hospital discharge up to 4 weeks and 6 weeks, using either low-molecular-weight heparin (LMWH), warfarin, or aspirin. In the reference strategy, antithrombotic prophylaxis was stopped at hospital discharge. Outcome measures included the number of PE prevented, major haemorrhages induced, overall costs in Euro (EUR) and specific costs generated by each PE prevented for all strategies.Extending prophylaxis up to 4 weeks after discharge was safe and cost saving for all prophylactic regimens, although LMWH was the most effective strategy. Our results were most sensitive to the rate of haemorrhages, the efficacy of treatment and its costs. Specifically, the number of PEs prevented exceeded that of haemorrhages induced if the efficacy of antithrombotic prophylaxis was 2:40% (assuming a low rate of haemorrhages of 0.1% per week), and 2:70% (assuming a high rate of haemorrhages of 0.25% per week). LMWH and warfarin remained cost saving unless their costs were more than doubled compared to that of baseline value. Although less effective than LMWH and warfarin, prophylaxis with aspirin was cost saving in all scenarios tested. Extending prophylaxis up to 6 weeks was also effective (the number of PEs prevented overwhelmed that of major haemorrhages induced), but only for the scenario of a low bleeding risk (0.1%/week). In this strategy, aspirin remained cost saving, while the costs for each PE prevented became high (EUR 10,000 to EUR 20,000) if the costs of LMWH and warfarin increased.After hip replacement, extending antithrombotic prophylaxis up to 4 weeks after hospital discharge is effective and cost saving. Although LMWH is the most effective strategy, warfarin, and to a lesser extent aspirin may be alternate options if ressources are a major concern.Extending prophylaxis up to 6 weeks is more risky in patients at high bleeding risk, and generates additional costs.
Keywords: Deep vein thrombosis; hip replacement; antithrombotic prophylaxis; cost-effectiveness